2019
DOI: 10.1136/postgradmedj-2019-136409
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic value of biomarkers in acute myocardial infarction

Abstract: The incidence of acute myocardial infarction (AMI) has been increasing rapidly in recent years, seriously endangering human health. Cardiac biomarkers play critical roles in the diagnosis and prognosis of AMI. Troponin is a highly sensitive and specific biomarker for AMI diagnosis and can independently predict adverse cardiac events. Other biomarkers such as N-terminal B-type natriuretic peptide and C reactive protein are also valuable predictors of cardiovascular prognosis. Recently, several novel biomarkers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 93 publications
4
52
0
1
Order By: Relevance
“…Further comparison of HIF-1 and VEGF levels between the routine therapy group and the study group showed that the content in the study group was higher than that in the routine therapy group, suggesting that the combination of atorvastatin and routine therapy increased the concentrations of HIF-1 and VEGF. HIF-1 is the key factor of cell regulation in hypoxia (21). HIF-1 can stimulate the release of VEGF-A when cells are anoxic.…”
Section: Discussionmentioning
confidence: 99%
“…Further comparison of HIF-1 and VEGF levels between the routine therapy group and the study group showed that the content in the study group was higher than that in the routine therapy group, suggesting that the combination of atorvastatin and routine therapy increased the concentrations of HIF-1 and VEGF. HIF-1 is the key factor of cell regulation in hypoxia (21). HIF-1 can stimulate the release of VEGF-A when cells are anoxic.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of hs-cTn analysis, diagnostic sensitivity has been further improved; however, specifi city is relatively reduced [3]. Myoglobin is an early and sensitive marker it starts to rise in the blood 2 hour after following onset of myocardial necrosis but the specifi city for the diagnosis MI to some extent [4]. Other marker CK-MB that is specifi c and starts to elevate within 3-4 hour after onset of myocardial injury but sensitivity is not higher [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also reported that hs-CRP was a diagnostic biomarker for AMI and could potentially refl ect the extent of myocardial injury in STEMI [4,9]. So we need to a better marker for early detection that sensitivity and specifi city should be high and decline these limitations.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of high-sensitivity cTn (hs-cTn) analysis, diagnostic sensitivity has been further improved, however, specificity is relatively reduced since serum cTn levels were also increased in renal failure or pulmonary embolism patients without MI 6, 7. Other myocardial necrosis biomarkers, such as creatine kinase MB (CK-MB) and myoglobin (MYO), were similarly lacked cardiac specificity for diagnosing myocardial infarction to some extent 8, 9. These limitations and urgent clinical requirements have promoted identifications of novel biomarkers for MI, including neuroendocrine, inflammatory, genetic and molecular biomarkers.…”
Section: Introductionmentioning
confidence: 99%